Avaliação de inibidores verdes microemulsionados na inibição à corrosão do aço carbono AISI 1020 - Almeida, Cássia Carvalho de (2012)
In general, among the corrosion inhibitors surfactants are the most commonly used compounds, because they are significantly effective by forming protective films on anodic and cathodic areas. In this study, microemulsions containing he biodegradable saponified coconut oil as surfactant (SME-OCS) was used as green corrosion inhibitors. With this purpose, methanolic extracts of Ixora coccinea Linn (IC) and a polar fraction rich in alkaloids (FA) obtained from Croton cajucara Benth solubilized in the SME-OCS system were examined in the presence of AISI 1020 carbon steel, in saline solution (NaCl 3,5 %). The efficiency of corrosion inhibition of IC and FA were evaluated in the following microemulsions: SME-OCS-IC and SME-OCS-FA. The microemulsion system SME-OCS in the presence and absence of IC and FA was assessed by measurements of weight loss and the electrochemical method of polarization resistance, with variation in the concentration of IC and FA (50 - 400 ppm), showing significant results of corrosion inhibition (83,6 % SME-OCS; 92,2 % SME-OCS-FA; and 95,3 % SME-OCS-IC)